KEWARGANEGARAAN INDONESIA DAN KARAKTERISTIK WNI DALAM KONTEKS INDIVIDU YANG BERANEKARAGAM - Siregar, Rozi; Zulhidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses Indonesian citizenship and the characteristics of Indonesian citizens within the context of diverse individuals. The purpose of this research is to understand the concepts of citizens and citizenship, the importance of citizenship status, sources of information regarding citizens and residents of Indonesia, and the importance of population data and civil registration in state life. The research method used is library research by reviewing various scientific sources such as books, journals, and relevant official documents. The results show that citizenship is a legal relationship between individuals and the state that creates rights and obligations for every citizen. Indonesia, as a multicultural country, possesses ethnic, cultural, linguistic, and religious diversity which becomes the main characteristic of Indonesian citizens. In addition, official documents such as identity cards, family cards, birth certificates, and passports play an important role as sources of population information and legal proof of citizenship status. Population data and civil registration also function as the basis for public services, legal protection, and national development planning. Therefore, orderly and accurate population administration